Redundant Vasodilator Pathways Underlying Radial Artery Flow-Mediated Dilation Are Preserved in Healthy Aging - Kevin D. Ballard; Michael E. Tschakovsky; Amanda L. Zaleski; Donna M. Polk; Paul D. Thompson; Francis J. Kiernan; Beth A. Parker (Journal of Aging Research)
Background. Blocking nitric oxide (NO) and vasodilator prostanoids (PN) does not consistently reduce flow-mediated dilation (FMD) in young adults. The impact of aging on the contribution of NO and PG to FMD is unknown. Methods. FMD was measured in older adults (n=10, 65±3 y) after arterial infusion of saline, N(G)-monomethyl-L-arginine (L-NMMA), and ketorolac + L-NMMA. Data were compared to published data in young adults. Results. L-NMMA reduced FMD in older adults (8.9±3.6 to 5.9±3.7%) although this was not statistically significant (P=0.08) and did not differ (P=0.74) from the reduction observed in young adults (10.0±3.8 to 7.6±4.7%; P=0.03). Blocking PN did not affect FMD in young or older adults. In older adults, L-NMMA reduced (n=6; range = 36–123% decrease), augmented (n=3; 10–122% increase), or did not change FMD (n=1; 0.4% increase). After PN blockade, FMD responses were reduced (n=2), augmented (n=6), or unaffected (n=1). Conclusions. NO or PN blockade did not consistently reduce FMD in healthy older adults, suggesting the existence of redundant vasodilator phenotypes as observed previously in young adults.